Disrupting Dysconsciousness: Confronting Anti-Blackness in Educational Leadership Preparation Programs. Issue 1 (January 2021) - Waite, Shannon R.
This article examines liberatory pedagogical practices utilized in graduate level courses offered within an educational leadership preparation program (ELPP). The research explores how these tools support the development of culturally responsive school leadership and actively anti-racist leaders in a program purporting to develop social justice-oriented school leaders. The author analyzes data collected from student course evaluations (SCEs) and assignments in courses taught across two years. Findings indicate that students perceived the liberatory pedagogical practices employed within the course to be vital in pushing them towards disrupting the pathologies of racism and anti-Blackness cultivated during their primary through post-secondary schooling experiences. The findings also indicated that students responded positively to the use of liberatory pedagogical practices and frameworks that centered race and explicitly used race language.